Enzymatic valorization process of yellow cocoon waste for production of antioxidative sericin and fibroin film. Issue 4 (20th November 2020) - Yakul, Kamon; Kaewsalud, Tanyawat; Techapun, Charin; Seesuriyachan, Phisit; Jantanasakulwong, Kittisak; Watanabe, Masanori; Takenaka, Shinji; Chaiyaso, Thanongsak
Abstract: BACKGROUND: Cocoon waste, solid waste from the silk industry, is currently utilized as low‐cost spun silk yarn. In this study, the enzymatic valorization process of yellow cocoon waste to produce antioxidative sericin hydrolysate and fibroin film was demonstrated. RESULTS: The enzymatic process involving thermostable alkaline protease from Bacillus halodurans SE5 (protease_SE5) was superior to the conventional high temperature and high pressure and 0.5% Na2 CO3 processes. Protease_SE5 produced sericin hydrolysate with high peptide concentration (0.335 mg mL –1 ) and provided degummed fibroin with a complete structure. Sericin hydrolysate from protease_SE5‐assisted hydrolysis showed remarkable radical scavenging activities on ABTS, DPPH and FRAP assays with 602, 3.90 and 24.8 μmol Trolox equivalents (TE) g −1 protein, respectively. After ultrafiltration and size‐exclusion chromatography, two active fractions (F1 and F2) were obtained from sericin hydrolysate with ABTS radical scavenging activity of 2120 and 3289 μmol TE g −1 protein, respectively. Identification of bioactive peptides by de novo sequencing was conducted, and seven candidate peptides were identified with high content of key antioxidative amino acids (His, Phe, Trp, Tyr and Arg) in the sequences. Moreover, bioactivities of several of the peptides were predicted by bioinformatics databases. Besides, the mechanical properties of enzyme‐derived fibroin film were also improved, with tensile strength and elongation at break of 62.1 MPa and 3.6% in the dry state, and 8.5 MPa and 140% in the wet state. CONCLUSION: This enzymatic process could be an effective way for valorizing cocoon waste. The value‐added products from agricultural waste have promising applications in food, pharmaceutical and biomedical materials. © 2020 Society of Chemical Industry (SCI)